Isolation and Identification of Etiological Agent of Pulmonary Tuberculosis in Patients Visiting National Tuberculosis Centre, Thimi Bhaktapur - Singh, Sudeep; Dhakal, D.; Subba, S.; Khagi, A. R.; Lekhak, B.; Singh, A.; Shrestha, K. B.; Bajracharya, A. (Journal of Nepal Health Research Council, 2009)
Not uploaded.Key words: M.tuberculosis; Niacin; Nitrate; Catalase; PNBDOI: 10.3126/jnhrc.v5i2.2472Journal of Nepal Health Research Council (JNHRC) Vol. 5, No.2, October 2007 55-61